Capital structure, corporate taxation and firm age - Michael Pfaffermayr; Matthias Stöckl; Hannes Winner (University of Innsbruck, Department of Public Finance, 2008)
This paper analyzes the relationship between capital structure, corporate taxation and firm age. We adapt a standard model of optimal capital structure choice under corporate taxation, focusing on the financing and investment decisions a young firm is typically faced with. Our model allows to derive testable hypotheses about the relationship between corporate taxation, a firm's age and its debt to asset ratio. To test these hypotheses empirically, we use a cross-section of 405,000 firms from 35 European countries and 126 NACE 3-digit industries. In line with previous research, we find that a firm's debt ratio increases with the corporate tax rate. Further, we observe that older firms exhibit smaller debt ratios than their younger counterparts. Finally, consistent with our theoretical expectation, we find a positive interaction effect between corporate taxation and firm age, indicating that the impact of corporate taxation on debt is increasing over a firm's life-time.
Keywords: H20; H32; G32; C31; 330; corporate taxation; capital structure; firm age; Unternehmensbesteuerung; Kapitalstruktur; Unternehmenserfolg; Europa